Perancangan Antena Mikrostrip Frekuensi Ganda Menggunakan Metode Y Slot untuk Sistem Komunikasi 5G dan WiFi - Wirdatul Usrah; syah alam; indra Surjati (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
This research proposes the design of dual-frequency microstrip antenna using the Y slot method. Antenna are designed with a working frequency of 3,5 GHz for 5G and 5 GHz communication systems for Wi-Fi using RT duroid 5880 substrates with a constant value in electricity of 2,2, a thickness of 1,575 mm and a loss of tangents of 0,009. The Y slot method is used to generate antenna that can work on dual bands and then add inset feed to the antenna in order to optimize the return loss value of the proposed antenna. From the design and simulation has been successfully obtained antennas that can work at frequencies 3,5 GHz and 5 GHz. The addition of inset feed on the antenna results in a return loss value for the frequency of 3,5 GHz which is -17,86 dB and a frequency of 5 GHz which is -36,27 dB. Inset feed renching on antenna design using Y slot method successfully optimizes return loss value at 5 GHz frequency of 54,34% compared with single element antenna.